Picture perfect: '4D' ultrasound and the commoditisation of the private prenatal clinic. (July 2017) - Thomas, Gareth M
Non-medical 'four-dimensional' ultrasound is commercially advertised as promoting maternal 'bonding', providing reassurance and tendering entertaining experiences for expectant parents. Despite the proliferation of this technology, it has not yet been subjected to sufficient social scientific attention. Drawing on an ethnography of a private prenatal clinic in the United Kingdom, I explore how four-dimensional scans, providing detailed real-time images of a foetus, have transformed the prenatal clinic into a site of consumption. I argue that the discourse present in four-dimensional scans and the materiality of the clinic achieve two things. First, they blur the boundary between clinical and non-clinical practices. This must be carefully negotiated by professionals who perform serious emotional labour to balance the delicate tension of offering expertise and medically based reassurance with providing a joyful experience for parents as consumers. Second, the four-dimensional scan and clinic's materiality promote the notion of 'perfection', particularly around the idealised family and future body. I conclude by reflecting on how such non-medical technologies play a central role in the commoditisation of pregnancy, bodies, the family and prenatal care in an increasingly consumer-led market.